DETECTION OF MYCOPLASMA GALLISEPTICUM IN EXPERIMENTALLY INOCULATED LAYER BIRDS BY IMMUNOHISTOCHEMISTRY - M. Rauf; Z. I. Chaudhary; M. Younas; A. A. Anjum; H. M. Khan; M. A. Ali (Journal of Animal and Plant Sciences, 2014)
Mycoplasma gallisepticum (MG), causative agent of chronic respiratory disease (CRD), is transmitted by both vertical and horizontal routes. Aim of the present study was to analyze the focal infection by immunohistochemistry. Two hundred (200) white leg horn layer birds, divided in four groups (n=50, each) were experimentally infected with MG by aerosol, intra-tracheal or oral routes respectively in relation to control group. Birds were monitored daily for the appearance of clinical signs of disease. Ten birds from each group were randomly selected and slaughtered on 4th, 11th, 18th, 25th and 32nd days post infection. Gross lesions including air sacculitis, salpingitis, putrefied eggs in ovary, and hemorrhages in trachea and lungs were detected. Histopathology of trachea, lungs and oviduct showed early onset of MG infection by aerosol, followed by intra tracheal and oral route. The infection through aerosol and intra-tracheal route was found to be severe as compare to oral route. Immunohistochemical examination of paraffin embedded sections of trachea, lungs and oviduct revealed the presence of MG in lungs and oviduct. Out of 150 MG infected birds 44 (29%) were positive on immunohistochemical examination. Highest percent infection was observed by intra-tracheal route (21/50) followed by aerosol (16/50) and per-oral (7/50).  Result insinuates the importance of immunohistochemistry and relation between route of infection and disease severity of MG in birds.
Keywords: Mycoplasma gallisepticum; CRD; gross lesions; histopathology and Immunohistochemistry